2022
DOI: 10.1007/s12144-022-03450-y
|View full text |Cite
|
Sign up to set email alerts
|

Psychological ownership and knowledge behaviors during a pandemic: role of approach motivation

Abstract: The purpose of this article is to understand the relationship between psychological ownership, knowledge sharing, knowledge hiding and employee motivation in knowledge intensive organizations. We take employee motivation in terms of approach motivation and avoidance motivation and examine moderating role of the former in case of the psychological ownership – knowledge sharing relationship, and the latter in case of the psychological ownership – knowledge hiding relationship. We examine these relationships on d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 64 publications
1
4
0
Order By: Relevance
“…Our study also confirms the influence of psychological ownership on KH as previous studies (e.g. Batool et al, 2022;Peng, 2013;Singh, 2019) have established. The study has confirmed the ownership feeling for knowledge is another proximal variable that predicted the KHB of the students.…”
Section: Discussion Of Findingssupporting
confidence: 92%
See 2 more Smart Citations
“…Our study also confirms the influence of psychological ownership on KH as previous studies (e.g. Batool et al, 2022;Peng, 2013;Singh, 2019) have established. The study has confirmed the ownership feeling for knowledge is another proximal variable that predicted the KHB of the students.…”
Section: Discussion Of Findingssupporting
confidence: 92%
“…That is, the perception of a sense of belonging, accountability and territoriality could result in increasing KHB. For instance, Batool et al (2022) found that stronger feelings of psychological ownership led to both positive work behaviour (i.e. knowledge sharing) as well as negative work behaviour (i.e.…”
Section: The Psychological Ownership Theory (Pot) and Khmentioning
confidence: 99%
See 1 more Smart Citation
“…Psychological ownership is an attitude to which individuals feel that the ownership of target or some part of target is theirs only [ 29 , 30 ]. Ownership can theorize both as psychological state or an objective perspective [ 31 , 32 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…This resulted in limited economic activity besides interaction among humans affecting students, professionals as well as people from all walks of life. Universities and their faculty had to come up with newer and hybrid ways of teaching using technology (Adedoyin and Soykan, 2023; Malik et al , 2022); organisational employees’ motivation and knowledge-sharing capacities were influenced by that (Batool et al , 2022), as well as people and economies faced poverty (Suryahadi et al , 2020). However, soon after, organisations, individuals and governments found ways out of the deadlock and thrived in their ways.…”
Section: Special Section – Human Capital Management and Technology In...mentioning
confidence: 99%